PENGARUH PEMBELAJARAN DARING DIMASA PANDEMI COVID 19 TERHADAP PRESTASI AKADEMIK MAHASISWA KEPERAWATAN - Ismailinar Ismailinar; Muzakkir Muzakkir; Fitriana Dewi; Said Taufiq (Poltekkes Kemenkes Aceh, 2023)
The government issued a Circular of the Ministry of Education and Culture of the Directorate of Higher Education Number 1 of 2020 concerning preventing the spread of Covid-19 in the world of education. The government has banned universities from conducting face-to-face lectures and ordered them to hold online lectures or learning. Research Objectives to determine the effect of online learning during the Covid 19 pandemic on the academic achievement of students of the North Aceh Nursing Study Program. This type of research is quantitative with a survey design. This research was conducted at the North Aceh Nursing Study Program. This research was conducted for 6 days. The population in this study were nursing students level 1 and 2 with a total sample of 140 students. The results of the study showed a decrease in GPA of 0.26 in online learning.